Fall of the Sultanate : The Great War and the End of the Ottoman Empire, 1908-1922 - Gingeras, Ryan (Oxford Oxford University Press, 2016)
After 600 years of ruling over the peoples of North Africa, the Balkans and Middle East, the collapse of the Ottoman Empire encompassed a series of wars, insurrections, and revolutions spanning the early 20th century, the political, economic, social, and international forces of which are detailed in this study.
Include Bibliography and Index
Keywords: World War, 1914-1918 -- Turkey -- History -- Revolution, 1918-1922